Spatial distribution of radiated seismic energy from earthquakes in Taiwan and surrounding regions. (December 2020) - Lin, Ting-Li; Mittal, Himanshu; Wu, Cheng-Feng; Huang, Yun-Hsuan
Graphical abstract: Highlights: Earthquake energy provides a different perspective of lithospheric strength as compared to earthquake numbers. 98% of the events occurred within 100 km depth; while, the remaining 2% were located at deeper depths. The earthquakes occurring to a depth of 100 km contribute about 88% of the energy in and around Taiwan. The upper mantle may play an important role in energy distribution, though most of the earthquakes occurred in the crust. The lower crust and upper mantle may control plate-driving forces, causing deformation. Abstract: The radiated energy during earthquakes is one of the essential characteristics that have a significant impact on human lives. The study of the released energy during earthquakes and their distribution may provide a detailed knowledge about the driving forces. In the present work, the earthquakes having magnitude (ML ) between 1.98 and 7.3 that occurred between 1994 and 2017 in and around Taiwan between the latitudes 21.5⁰N – 25.5⁰N and longitudes 119⁰E – 123⁰E are used to study the spatial distribution of energy in Taiwan. The maximum reported focal depth for the used earthquakes is 320 km. ML is converted to energy with necessary correction in the existing conversion formula using a correction factor based on the energy of two earthquakes that occurred in Taiwan. It is found that the distribution of earthquake numbers and energy is not uniform. In particular, 98% of the events occurred within 100 km depth; while, the remaining 2% were located at deeper depths. Most of the events, about 65% of the total earthquakes are confined to the upper 20 km depth. The earthquakes occurring to a depth of 100 km contribute about 88% of the energy in and around Taiwan. Only a few earthquakes occurring beyond 100 km depth contribute to around 12% of total released energy. The highest energy release is attributed to the eastern subduction along the Ryukyu trench. Our results show that the lower crust and upper mantle may play an essential role in energy distribution, though most of the earthquakes have occurred in the upper crust. Therefore, the temporal and spatial distributions of seismic energy release will be further studied to reveal the characteristics of the seismogenic zone in the future.